Distribution of Serogroups and Genotypes among Neisseria Meningitidis Strains in Malaysia - Kuppusamy, Puvanesvari (2009)

(untitled)
Neisseria meningitidis causes meningococcal disease, a life threatening illness with an annual incidence of 1 to 1000 per 100,000 population in different parts of the world and humans are the only known host to this organism. The fastidious nature of the organism and the common practice of starting antibiotic treatment prior to sample collection pose a challenge in culture based diagnosis of this organism. Typing methods based on molecular techniques are also replacing the phenotypic methods such as serogrouping owing to frequent lack of expression of the surface antigens as well as the unavailability of the typing antisera. Increased reports of N. meningitidis showing decrease susceptibility to penicillin, the drug of choice in meningococcal disease treatment has also raised some concern. In this study, a novel multiplex PCR assay was developed to identify N. meningitidis, detect its capsule (an important virulence factor in bloodstream invasion) and determine its susceptibility to penicillin. In addition, a multiplex PCR assay to determine the serogroups A, B, C, Y and W135 as well as a duplex PCR assay to determine the serogroups X and Z were adapted and optimized from previously published work. These assays were used against 123 N. meningitidis strains (114 carrier strains and 9 clinical strains). All the strains had first been identified by biochemical reactions, serogrouped by the slide agglutination technique and tested for susceptibility to penicillin by the Etest® method. The gene targeted for identification (porA) was detected in all the 123 test strains and all 7 reference meningococci strains but not in other Neisseria species, making it a good marker for identification. The capsule gene (ctrA gene) was detected in 8/9 (88.9%) clinical strains and 35/114 (30.7%) carrier strains. The lack of capsule among the carrier strains, is high but non-capsulated strains among carriers is a common phenomenon. The susceptibility to penicillin gene (penA) was detected in 8/9 (88.9%) clinical strains and 74/114 (64.9%) carrier strains, thus 33.3% of all strains showed intermediate resistance to penicillin. Detection of serogroups by PCR (genogrouping) showed an increase of 86% when compared to the slide agglutination technique, and this increase was seen only among the carrier strains. 21.2% of the strains were genogroupable showing predominance of serogroups B and W135 in clinical strains and Y, B, Z, W135 and X among carrier strains (in decreasing order).Multilocus Sequence Typing (MLST) was used to genotype all the clinical strains and 71 of the carrier strains. A total of 32 sequence types (STs) of which 21 novel STs unique to Malaysia were found in this study showing a population of high genetic diversity. Of the 21 novel STs, 17 were unique for the carrier strains while 3 were unique for the clinical strains. Only one novel ST, ST7129 was found in both the carrier and clinical strains. Six clonal complexes of which two were of hyper invasive lineage, ST-11 Complex/ET-37 Complex (2.6%) and ST-41/44 Complex/ Lineage 3 (20.2%) were detected among the strains. Burst analysis identified three ancestral genotypes among the studied strains. These results indicate potential application of MLST to the study of meningococcal epidemiology and evolution in Malaysia. While the genogrouping results show the potential of using these multiplex PCR assays in detecting the serogroups of the N. meningitidis strains, especially strains designated as “non- serogroupable” by the conventional methods.